Participation in extracurricular activities for children with and without siblings with Autism Spectrum Disorder - Falkmer, Torbjorn; Wigston, C.; Falkmer, M.; Vaz, S.; Parsons, R. (2016)
Objective: To compare the number, frequency, enjoyment and performance in extracurricular activities of siblings of children with autism spectrum disorders (ASD) to their typically developing (TD) peers, and to identify differences between actual and desired participation. Methods: A case-control study with 30 siblings of children with ASD and 30 siblings of TD children was conducted using the Paediatric Interest Profiles and a questionnaire. Results: Siblings of children with ASD participated in fewer extracurricular activities than those with TD siblings. ASD symptoms were significantly associated with the sibling participating in fewer extracurricular activities. Children with TD siblings had higher enjoyment scores in relaxation activities than children with siblings with ASD. Conclusion: While results were mainly positive, some differences indicated that having a sibling with ASD may impact participation in extracurricular activities. Assessments of participation barriers, as well as support to minimise participation restrictions among siblings of children with ASD are required.